TINJAUAN YURIDIS PELAKSANAAN KEWENANGAN BPD (BADAN PERMUSYAWARATAN DESA) DI DESA KASANG LIMAU SUNDAI KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI BERDASARKAN PERDA NOMOR. 1 TAHUN 2009 - Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
This research was conducted in Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency. This type of research is a sociological study of a study in the form of empirical studies to find theories about the process and about the workings of law in society. Nature of this research is descriptive research is to provide thorough data about peoples, circumstances or other symptoms. The results showed that the implementation of the Village Consultative Body authority in the organization of government in the Kasang Limau Sundai Village, Kuantan Hilir Seberang District, Kuantan Singingi Regency according to Regulation No. 1 of 2009 have not been able to bring the regulations the new village, because the members of the BPD has not been submitted draft regulations and material to the village government. Constraints faced by BPD Kasang Limau Sundai in doing authority to draft village regulations are educational background factors BPD is still low, the lack of understanding of the procedures and the BPD Perdes formation mechanism, and the lack of cooperation with the village government. Attempts to do BPD Kasang Limau Sundai to overcome obstacles in the implementation of the authority is to follow the training and seminars related to the procedures for the formation mechanism of the village or the regulations relating to the empowerment of rural communities. Moreover, it also can be a way members of the BPD over again deepen the knowledge of the law by reading books related to the formation technique of legislation, as well as by increasing cooperation with government village that BPD can equally with the village government in the deliberations and discussions held, and took the decision to make a village regulations in order to achieve progress in the future well-being of rural communities.Keywords: Implementation, Authority, Village Consultative Body (BPD)